A modified sulfide solid electrolyte and a preparation method and application thereof

CN122968290APending Publication Date: 2026-10-23NANJING LITHIUM SOURCE NANO TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611218615.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]发明目的:本发明的目的是提供一种界面稳定、抑制 Li2S、维持高离子电导率、提升长循环与临界电流密度的改性硫化物固态电解质及其制备方法和应用,解决现有技术中硫化物固态电解质与锂金属负极界面副反应严重、离子电导率易下降、临界电流密度低的问题

Benefits of technology

[0020]有益效果:与现有技术相比,本发明具有如下显著优点:本发明的预锂化双巯基三嗪类添加剂,通过预锂化结构避免了添加剂原位夺锂副反应,同时利用双巯基与三嗪双亲锂位点,在硫化物固态电解质与锂金属负极界面原位构建了富磷、贫Li2S的稳定SEI层,有效抑制了电解质界面分解、锂空位形成和锂枝晶生长,显著降低界面阻抗,从而形成更稳定的界面。在Li/Li对称电池中,该策略可使临界电流密度提升,实验数据表明,实施例2的离子电导率达到8.76 mS/cm,较未改性的纯LPSC电解质提升了约56%,临界电流密度从1.0mA/cm2提升至2.0 mA/cm2,在0.5C倍率下循环100圈后容量保持率可达89.73%,远优于纯LPSC电解质的75.91%。另外该原料易得、制备工艺简单,可通过一步预锂化与机械研磨实现规模化应用,兼具成本优势与产业化潜力,为硫化物全固态锂金属电池的界面稳定提供了一种全新、高效的改性策略。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968290A_ABST
    Figure CN122968290A_ABST
Patent Text Reader

Abstract

The application discloses a modified sulfide solid electrolyte and a preparation method and application thereof, and the modified sulfide solid electrolyte comprises a sulfide solid electrolyte and a pre-lithiation additive dispersed in the sulfide solid electrolyte, the pre-lithiation additive is an organic lithium salt with a bismercapto-triazine skeleton, contains a triazine ring and two sulfur-lithium groups, and is obtained by converting mercapto groups in a bismercapto-triazine compound into the sulfur-lithium groups under alkaline conditions. The application further provides a preparation method of the modified material. The pre-lithiation treatment avoids the capture of Li + in the electrolyte skeleton by un-pre-lithiated mercaptans, maintains the integrity of the crystal structure, and the appropriate amount of the additive can increase the ionic conductivity to 8.76 mS / cm, the critical current density to 2.0 mA / cm 2 , and the cycle capacity retention rate is significantly improved, so that the interface stability and the ionic conductivity are synergistically improved, and the process is simple and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology, specifically to a modified sulfide solid electrolyte, its preparation method, and its application. Background Technology

[0002] Sulfide solid electrolytes have become a research hotspot in the field of all-solid-state lithium metal batteries due to their high ionic conductivity, good flexibility, and compatibility with lithium metal anodes. Among them, LPSC sulfide solid electrolytes have attracted widespread attention due to their excellent comprehensive performance. However, sulfide electrolytes have obvious defects: firstly, they have a narrow electrochemical stability window and undergo severe side reactions with lithium metal anodes, generating a large amount of insulating Li2S, which leads to a sharp increase in interfacial impedance; secondly, lithium deposition is uneven, which easily forms dendrites and causes short circuits; and thirdly, traditional organic additives (such as polymers) can significantly reduce ionic conductivity, making it difficult to balance stability and conductivity.

[0003] Existing technologies attempt to employ strategies such as inorganic doping and artificial interface layers, but these suffer from problems such as complex processes, high costs, and difficulties in large-scale scaling. Small-molecule organic thiols, due to their mild film-forming properties, strong lithium affinity, and low addition amounts, have become a preferred direction for interface modulation. However, molecules such as trithiocyanuric acid (TCA), benzenetrithiol (TTB), and dimercaptothiadiazole (DMTD) have been extensively reported, and their structures and application scenarios highly overlap, limiting the scope for innovation. Furthermore, unlithiated thiols readily abstract Li from the electrolyte. + This can damage the electrolyte structure and reduce conductivity. Therefore, developing novel additives with entirely new structures that are not disclosed in existing technologies, can stably pre-lithiate, do not damage the electrolyte, and produce more uniform film formation, thereby improving the interface stability, ionic conductivity, and long cycle life of sulfide solid-state batteries, has become an urgent technical problem to be solved in this field. Summary of the Invention

[0004] Purpose of the invention: The purpose of this invention is to provide a modified sulfide solid electrolyte with stable interface, suppressing Li2S, maintaining high ionic conductivity, and improving long-cycle and critical current density, as well as its preparation method and application, to solve the problems of severe side reactions at the interface between sulfide solid electrolytes and lithium metal anodes, easy decrease in ionic conductivity, and low critical current density in the prior art.

[0005] Technical Solution: The modified sulfide solid electrolyte of this invention comprises a sulfide solid electrolyte and a pre-lithiation additive; the pre-lithiation additive is an organolithium salt with a dithiol triazine skeleton, its molecular structure containing a triazine ring and two lithium sulfide groups (-SLi). The pre-lithiation additive is obtained by converting the thiol groups (-SH) in the dithiol triazine additive into lithium sulfide groups (-SLi) under alkaline conditions. The pre-lithiation additive is dispersed on the particle surface of the sulfide solid electrolyte.

[0006] Preferably, the alkaline condition is pH=10±0.3.

[0007] Preferably, the dithiotriazine additive includes at least one of 2-amino-4,6-dithio-1,3,5-triazine ADT and 2-methyl-4,6-dithio-1,3,5-triazine MDT.

[0008] Preferably, the ratio of the sulfide solid electrolyte to the pre-lithiation additive is 1:0.01~0.03 by weight.

[0009] Further preferably, the sulfide solid electrolyte is Li 5.4 PS 4.4 Cl 1.6 .

[0010] The preparation method of the modified sulfide solid electrolyte of the present invention includes the following steps: Preparation of pre-lithiation additive: Dissolve dithiol triazine additive and LiOH in deionized water, the pH of the mixed solution is 10±0.3, then stir until clear, dehydrate under vacuum and dry to obtain pre-lithiation additive; (2) Preparation of sulfide solid electrolyte: Lithium sulfide Li2S, phosphorus pentasulfide P2S5 and lithium chloride LiCl are mixed in a preset ratio and then mechanically crushed to obtain a uniformly dispersed mixed powder. The mixed powder material is then sintered to obtain a sulfide solid electrolyte. (3) Grind and mix the pre-lithiation additive obtained in step (1) with the sulfide solid electrolyte obtained in step (2) to obtain the modified sulfide solid electrolyte.

[0011] Preferably, in step (1), the molar ratio of the dithiol triazine additive to lithium hydroxide is 1:2.

[0012] Preferably, in step (2), the sulfide solid electrolyte is Li 7-x PS 6-x Cl x The molar ratio of Li2S∶P2S5∶LiCl is (7-2x):1:2x, where 1.3<x<1.7.

[0013] Preferably, in step (2), the sintering temperature is 480~500℃, the heating rate is 0.5~2℃ / min, and the calcination time is 6~12h.

[0014] Preferably, in step (3), the mass ratio of the sulfide solid electrolyte to the pre-lithiation additive is 1:0.01~0.03.

[0015] Preferably, in step (1), the vacuum drying temperature is 80°C and the vacuum drying time is 8~12h.

[0016] Preferably, in step (2), the mixing and crushing process in the mechanical crushing step of the raw materials is as follows: lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) mixed according to the preset ratio are placed in a crusher and mixed and crushed under nitrogen atmosphere protection. The duration of the mixing and crushing operation is 10 minutes to obtain uniformly dispersed mixed powder.

[0017] More preferably, in step (2), the crushing operation is to grind powder for 2 minutes each time, and grind powder for a total of 5 groups. During the interval between each group, scraping is performed to prevent the powder from sticking to the wall and the mixture from being uneven due to excessive power of the crusher.

[0018] More preferably, in step (3), the mixture is ground and mixed under a protective atmosphere until the particle size D50 < 10 μm to obtain a modified sulfide solid electrolyte.

[0019] The application of the modified sulfide solid electrolyte described in this invention in the preparation of solid-state batteries.

[0020] Beneficial Effects: Compared with the prior art, the present invention has the following significant advantages: The pre-lithiated dithiol triazine additive of the present invention avoids the in-situ lithium abstraction side reaction of the additive through the pre-lithiation structure. At the same time, by utilizing the amphiphilic lithium sites of dithiol and triazine, a stable SEI layer rich in phosphorus and poor in Li2S is constructed in-situ at the interface between the sulfide solid electrolyte and the lithium metal anode, effectively suppressing electrolyte interface decomposition, lithium vacancy formation and lithium dendrite growth, significantly reducing interface impedance, and thus forming a more stable interface. In Li / Li symmetric batteries, this strategy can increase the critical current density. Experimental data show that the ionic conductivity of Example 2 reaches 8.76 mS / cm, which is about 56% higher than that of the unmodified pure LPSC electrolyte, and the critical current density is increased from 1.0 mA / cm. 2 Increased to 2.0 mA / cm 2 After 100 cycles at 0.5C, the capacity retention rate reaches 89.73%, which is far superior to the 75.91% of pure LPSC electrolyte. In addition, the raw material is readily available and the preparation process is simple. It can be scaled up through one-step pre-lithiation and mechanical grinding, which has both cost advantages and industrialization potential. It provides a new and efficient modification strategy for the interface stability of sulfide all-solid-state lithium metal batteries. Attached Figure Description

[0021] Figure 1 This is a molecular structure diagram of the pre-lithiation of the additive in an embodiment of the present invention.

[0022] Figure 2The image shows the XRD pattern of the modified sulfide solid electrolyte obtained in Example 1 of this invention. Detailed Implementation

[0023] The technical solution of the present invention will be further described below with reference to the accompanying drawings, embodiments, and comparative examples.

[0024] Example 1

[0025] (1) Preparation of pre-lithiation additives: 1.00 g ADT (6.93 mmol) and 0.33 g dry lithium hydroxide (13.86 mmol) were dissolved in 20 mL of deionized water and mixed. The pH of the solution was 10 ± 0.3. After stirring until the solution was clear, it was dehydrated under vacuum and dried under vacuum at 80 °C for 8 hours to obtain 1.24 g of white crystalline solid Li2ADT.

[0026] (2) Weigh lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride in a molar ratio of 19:5:16 and mechanically crush them for 10 min, scraping the material once between each batch. Place the crushed mixture into a quartz crucible and heat it to 480 ℃ at a rate of 0.5 ℃ / min under a nitrogen atmosphere. Hold the temperature for 12 h, and after cooling, crush and sieve the sintered material to obtain the sulfide solid electrolyte Li. 5.4 PS 4.4 Cl 1.6 .

[0027] (3) In a glove box, the sulfide solid electrolyte and the additive are ground and mixed at a weight ratio of 1:0.01 to obtain the modified sulfide solid electrolyte, wherein the particle size D50 of the modified sulfide solid electrolyte is <10 μm.

[0028] Example 2

[0029] The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 1; the only difference between it and Example 1 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.02 to obtain the modified sulfide solid electrolyte, wherein the particle size D50 of the modified sulfide solid electrolyte is <10um.

[0030] Example 3

[0031] The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 1; the only difference between it and Example 1 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.03 to obtain the modified sulfide solid electrolyte, wherein the particle size D50 of the modified sulfide solid electrolyte is <10um.

[0032] Example 4

[0033] (1) Preparation of pre-lithiation additives: 1.00 g MDT (6.98 mmol) and 0.33 g dry lithium hydroxide (13.96 mmol) were dissolved in 20 mL of deionized water and mixed. The pH of the solution was 10 ± 0.3. After stirring until the solution was clear, it was dehydrated under vacuum and dried under vacuum at 80 °C for 8 hours to obtain 1.24 g of white crystalline solid Li2MDT.

[0034] (2) Weigh lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) in a molar ratio of 19:5:16. Mix the three raw materials together and mechanically crush them. Each group is pulverized for 2 min, and the total mechanical crushing time is 10 min. The material is scraped off once between each group. The crushed mixture is placed in a quartz crucible and heated to 500℃ at a heating rate of 2℃ / min under a nitrogen atmosphere. The temperature is then maintained for 6 h. After cooling, the sintered material is crushed and sieved to obtain the sulfide solid electrolyte Li. 5.4 PS 4.4 Cl 1.6 .

[0035] (3) In a glove box, the sulfide solid electrolyte and the additive are ground and mixed at a weight ratio of 1:0.01 to obtain the modified sulfide solid electrolyte, wherein the particle size D50 of the modified sulfide solid electrolyte is <10 μm.

[0036] Example 5

[0037] The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 4; the only difference between it and Example 4 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.02 to obtain the modified sulfide solid electrolyte, and the particle size D50 of the modified sulfide solid electrolyte was <10 μm.

[0038] Example 6

[0039] The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 4; the only difference between it and Example 4 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.03 to obtain the modified sulfide solid electrolyte, wherein the particle size D50 of the modified sulfide solid electrolyte is <10um.

[0040] Example 7

[0041] The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 2; the only difference from Example 2 is that in step (2), lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride were weighed in a molar ratio of 4:1:3 to prepare the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 .

[0042] Example 8

[0043] The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 2; the only difference from Example 2 is that in step (2), lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride were weighed in a molar ratio of 42:10:28 to prepare the sulfide solid electrolyte Li 5.6 PS 4.6 Cl 1.4 .

[0044] Comparative Example 1 Lithium sulfide (Li₂S), phosphorus pentasulfide (P₂S₅), and lithium chloride (LiCl) were weighed in a molar ratio of 19:5:16. The three raw materials were mixed together and mechanically crushed, with each batch crushed for 2 minutes, for a total of 10 minutes. The mixture was scraped off once between each batch. The crushed mixture was then placed in a quartz crucible and heated to 500°C at a rate of 1°C / min under a nitrogen atmosphere. The temperature was then maintained for 8 hours. After cooling, the sintered material was crushed and sieved to obtain the sulfide solid electrolyte Li. 5.4 PS 4.4 Cl 1.6 .

[0045] Comparative Example 2 The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 1; the only difference between Example 1 and Example 2 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.005 to obtain the modified sulfide solid electrolyte.

[0046] Comparative Example 3 The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 1; the only difference between Example 1 and Example 2 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.05 to obtain the modified sulfide solid electrolyte.

[0047] Comparative Example 4 The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 4; the only difference between Example 4 and Example 4 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.005 to obtain the modified sulfide solid electrolyte.

[0048] Comparative Example 5 The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 4; the only difference between Example 4 and Example 4 is that in step (3), the sulfide solid electrolyte and the additive were ground and mixed at a weight ratio of 1:0.05 to obtain the modified sulfide solid electrolyte.

[0049] Comparative Example 6 The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 2; the only difference from Example 2 is that in step (2), lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride were weighed in a molar ratio of 23:5:12 to prepare the sulfide solid electrolyte Li 5.8 PS 4.8 Cl 1.2 .

[0050] Comparative Example 7 The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 2; the only difference from Example 2 is that in step (2), lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride were weighed in a molar ratio of 17:5:18 to prepare the sulfide solid electrolyte Li 5.2 PS 4.2 Cl 1.8 .

[0051] Comparative Example 8 The pre-lithiation additive and sulfide solid electrolyte were prepared according to the method of Example 2; the only difference between Example 2 and Example 2 is that in step (1), 1.227 g of trithiocyanuric acid (TCA, 6.93 mmol) and 0.50 g of dry lithium hydroxide (20.79 mmol) were dissolved in 20 mL of deionized water and mixed to react, resulting in 1.47 g of pale yellow crystalline solid Li3TCA.

[0052] The modified sulfide solid electrolytes obtained in all the above examples and comparative examples were subjected to the following electrochemical tests: (1) Ionic conductivity test 0.15 g of the sulfide solid electrolyte sample obtained in the embodiments and comparative examples of the present invention was placed in a battery mold and cold-pressed to obtain an electrolyte sheet, wherein the pressure applied during the cold pressing process was maintained at 255 MPa; an ion-blocking battery was obtained by assembling the stainless steel sheet, the electrolyte sheet, and the stainless steel sheet in that order; the ionic conductivity of the LPSC sulfide solid electrolyte sample used was evaluated by testing the electrochemical impedance spectroscopy of the obtained ion-blocking battery.

[0053] (2) Characterization of electronic conductivity 0.15 g of the sulfide solid electrolyte sample obtained in the embodiments and comparative examples of the present invention was placed in a battery mold and cold-pressed to obtain an electrolyte sheet, wherein the pressure applied during the cold pressing process was maintained at 255 MPa; an ion-blocking battery was obtained by assembling the stainless steel sheet, the electrolyte sheet, and the stainless steel sheet in that order; the electronic conductivity of the LPSC sulfide solid electrolyte sample used was evaluated by DC polarization testing.

[0054] (3) Critical current density test Critical current density test principle: Using a symmetrical battery (such as a lithium metal symmetrical battery), the current density is increased in alternating directions in a stepwise manner, and the change in battery voltage is observed. When the voltage suddenly drops to zero, the corresponding current density is the critical current density.

[0055] 0.15 g of the LPSC sulfide solid electrolyte sample obtained in this invention was placed in a battery mold and cold-pressed to obtain an electrolyte sheet, wherein the pressure applied during the cold pressing process was maintained at 255 MPa; a symmetrical battery was obtained by assembling the Li-In alloy, electrolyte sheet, and Li-In alloy in that order; and the battery was tested from an extremely low current density of 0.1 mA / cm². 2 Initially, charge-discharge cycles were performed for 0.5 hours at each current density. After the stabilization cycle was completed, the current density was gradually increased in fixed steps. The current density corresponding to the voltage suddenly dropping to 0 is the critical current density of the LPSC sulfide solid electrolyte sample.

[0056] (4) Cyclic performance test A method for preparing a solid-state battery is provided, specifically as follows: The positive electrode material is a mixture of high-nickel ternary material, a conductive agent, the aforementioned Li2ADT-LPSC solid electrolyte, and PTFE binder in a mass ratio of 70:2:27:1. The mixture is then placed in a ball mill and milled at 150 rpm for 3 hours to fibrousize the PTFE, yielding a mixture. The mixture is extruded into a roller press, and at 80°C, a solid electrolyte membrane with a thickness of 50 μm is obtained by adjusting the roller press gap. 0.15 g of the solid electrolyte sample of this invention is placed in a battery mold for cold pressing to obtain an electrolyte sheet, wherein the pressure applied during the cold pressing process is maintained at 255 MPa. The solid-state battery is then assembled in the order of solid electrolyte membrane, electrolyte sheet, and Li-In alloy. Room temperature cycling test method: The prepared solid battery is charged and discharged at 25℃ with a voltage range of 2.1-3.7V, and then charged and discharged at 0.1C for 1 cycle, followed by 0.5C for 100 cycles. The capacity retention rate of the 100th cycle is calculated as (discharge capacity of the 100th cycle / discharge capacity of the 1st cycle) * 100.

[0057] Table 1 shows the relevant performance test results of the sulfide solid electrolytes and solid batteries prepared in the examples and comparative examples.

[0058] In summary, the sulfide solid electrolyte of this invention exhibits high ionic conductivity and good interfacial stability, making this pre-lithiation additive highly suitable for high-rate and long-life all-solid-state battery systems. As... Figure 1 As shown in the molecular structure diagram of the pre-lithiation additive of the present invention, the two thiol groups (-SH) in the ADT molecule react with lithium hydroxide (LiOH) to be converted into lithium sulfide groups (-SLi), thus achieving pre-lithiation. Similarly, the two thiol groups (-SH) in the MDT molecule react with LiOH to be converted into lithium sulfide groups (-SLi). Figure 1 The molecular structure and preparation process of the two pre-lithiation additives of this invention are visually demonstrated, reflecting their structural novelty.

[0059] also Figure 2 The characteristic diffraction peaks of the modified sulfide solid electrolyte correspond perfectly to the Li6PS5Cl (LPSC) standard card (JCPDS Card No. 34-0688), with no obvious impurity peaks appearing. This indicates that the pre-lithiation additive Li2ADT of the present invention has not destroyed the crystal structure of the sulfide solid electrolyte. The modified sulfide solid electrolyte still maintains the complete silver-germanium sulfide crystal phase, which provides a structural basis for maintaining its high ionic conductivity.

[0060] The ionic conductivity, electronic conductivity, critical current density, and cycling performance of Li₂ADT-LPSC and Li₂MDT-LPSC modified sulfide solid electrolytes with different addition amounts were tested. The test results are shown in Table 1. As can be seen from the table, the pure LPSC electrolyte (Comparative Example 1) has an ionic conductivity of 5.61 mS / cm and an electronic conductivity of 8.13 × 10⁻⁶ mS / cm. -9 S / cm, critical current density is 1.0 mA / cm 2 The capacity retention rate after 100 cycles at 0.5C is 75.91%. Compared with pure electrolyte, the pre-lithiation additive of the present invention can significantly improve the overall performance of the electrolyte in the range of 1wt% to 3wt%.

[0061] Examples 2, 7, 8 and Comparative Examples 6, 7 are examples of sulfide solid electrolytes modified with the same additive Li2ADT. 7- x PS 6-x Cl x A series of performance tests were conducted, and the results are shown in Table 1. As can be seen from the table, the sulfide solid electrolyte Li2ADT-Li... 7-x PS 6-x Cl xThe ionic conductivity, electronic conductivity, critical current density, and capacity retention after 100 cycles at 0.5C for (1.3 < x < 1.7) are all superior to those of Li₂ADT-LPSC. 1.2 and Li2ADT-LPSC 1.8 The sulfide electrolyte Li2ADT-Li of this invention needs to be high-performance. 7-x PS 6-x Cl x When x is in the range of 1.3 to 1.7, the overall performance of the electrolyte can be significantly improved.

[0062] For the Li₂ADT modified system, when the addition amount was 2 wt% (Example 2), the ionic conductivity reached a maximum value of 8.76 mS / cm, which is about 56% higher than that of the pure electrolyte; the electronic conductivity decreased to 3.33 × 10⁻⁶ mS / cm. -10 The current density (S / cm) is reduced by about one order of magnitude compared to pure electrolytes; the critical current density is increased to 2.0 mA / cm. 2 After 100 cycles at 0.5C, the capacity retention rate was 89.73%, demonstrating optimal overall performance. However, when the additive dosage was too low or too high, the non-conductive phase introduced by the additive disrupted the continuity of the electrolyte framework, causing the ionic conductivity to drop to 4.78 mS / cm and the critical current density to be only 0.2 mA / cm². 2 .

[0063] For the Li₂MDT modified system, the performance change trend is consistent with that of the Li₂ADT system. When the addition amount is 2 wt% (Example 5), the ionic conductivity reaches the highest value of 8.49 mS / cm, which is about 51% higher than that of the pure electrolyte; the electronic conductivity decreases to 3.13 × 10⁻⁶ mS / cm. -10 The current density (S / cm) is reduced by about one order of magnitude compared to pure electrolyte; the critical current density is increased to 1.9 mA / cm. 2 Compared to pure electrolyte, it improves performance by 90%, and retains 89.24% of its capacity after 100 cycles at 0.5C, exhibiting the best overall performance. However, the modification effect significantly decreases when the addition amount is too low or too high.

[0064] The pre-lithiation additive in Comparative Example 8 is the publicly disclosed Li3TCA. This invention uses Li2ADT as the pre-lithiation additive. Compared to the trisubstituted fully lithiated Li3TCA, the disulfide lithium groups in Li2ADT molecules can stably supply active lithium to compensate for the irreversible capacity loss during the first cycle of the battery. The remaining free thiol groups can firmly bond to the surface of sulfide electrolyte particles, constructing an ultrathin, uniform, and mechanically tough interfacial passivation layer. This passivation layer can adapt to the volume changes of lithium metal during charge and discharge, effectively blocking interfacial side reactions between sulfides and metallic lithium, smoothing the lithium-ion deposition flux, and inhibiting lithium dendrite growth. Simultaneously, the modified Li2ADT can achieve uniform molecular-level coating without blocking ion transport channels between sulfide particles, exhibiting superior overall performance compared to Li3TCA in terms of interfacial impedance, battery cycle life, and system chemical stability.

[0065] The above test results demonstrate that the pre-lithiation additives Li2ADT and Li2MDT of this invention can significantly improve ionic conductivity and reduce electronic conductivity by optimizing the addition amount without damaging the crystal structure of the sulfide solid electrolyte, thereby greatly increasing the critical current density. Furthermore, their capacity after 100 cycles at a current density of 0.5C is significantly superior to other polymers. Therefore, an appropriate amount of pre-lithiation additive can improve electrolyte particle contact, reduce grain boundary impedance, and simultaneously form a stable low-impedance SEI layer at the lithium metal interface, ensuring uniform lithium-ion flux and suppressing lithium dendrite growth. This provides crucial material support for the large-scale application of high-performance sulfide all-solid-state lithium metal batteries.

Claims

1. A modified sulfide solid electrolyte, characterized in that, It includes a sulfide solid electrolyte and a pre-lithiation additive; the pre-lithiation additive is an organic lithium salt with a dithiol triazine skeleton, the molecular structure of which contains a triazine ring and two lithium sulfide groups (-SLi). The pre-lithiation additive is obtained by converting the thiol group (-SH) in the dithiol triazine additive into a lithium sulfide group (-SLi) under alkaline conditions.

2. The modified sulfide solid electrolyte according to claim 1, characterized in that, The dithiotriazine additives include at least one of 2-amino-4,6-dithio-1,3,5-triazine ADT and 2-methyl-4,6-dithio-1,3,5-triazine MDT.

3. The modified sulfide solid electrolyte according to claim 1, characterized in that, The ratio of the sulfide solid electrolyte to the pre-lithiation additive is 1:0.01~0.03 by weight.

4. The modified sulfide solid electrolyte according to claim 1, characterized in that, The sulfide solid electrolyte is Li 7-x PS 6-x Cl x , where 1.3 < x < 1.

7.

5. A method for preparing the modified sulfide solid electrolyte according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Preparation of pre-lithiation additive: Dissolve dithiol triazine additive and LiOH in deionized water, the pH of the mixed solution is 10±0.3, then stir until clear, dehydrate under vacuum and dry to obtain pre-lithiation additive; (2) Preparation of sulfide solid electrolyte: Lithium sulfide Li2S, phosphorus pentasulfide P2S5 and lithium chloride LiCl are mixed in a preset ratio and then mechanically crushed to obtain a uniformly dispersed mixed powder. The mixed powder material is then sintered to obtain a sulfide solid electrolyte. (3) Grind and mix the pre-lithiation additive obtained in step (1) with the sulfide solid electrolyte obtained in step (2) to obtain the modified sulfide solid electrolyte.

6. The preparation method according to claim 5, characterized in that, In step (1), the molar ratio of the dithiol triazine additive to lithium hydroxide is 1:

2.

7. The preparation method according to claim 5, characterized in that, In step (2), the sulfide solid electrolyte is Li 7-x PS 6-x Cl x The molar ratio of Li2S∶P2S5∶LiCl is (7-2x):1:2x, where 1.3<x<1.

7.

8. The preparation method according to claim 5, characterized in that, In step (2), the sintering temperature is 480~500℃, the heating rate is 0.5~2℃ / min, and the calcination time is 6~12h.

9. The preparation method according to claim 5, characterized in that, In step (3), the mass ratio of the sulfide solid electrolyte to the pre-lithiation additive is 1:0.01~0.

03.

10. The use of the modified sulfide solid electrolyte according to any one of claims 1 to 4 or the modified sulfide solid electrolyte prepared by the preparation method according to any one of claims 5 to 9 in the preparation of solid-state batteries.